Community and Stakeholder Participation in the Implementation of Corporate Social Responsibility Programs, Its Impact on Rural Communities - Abdurrozzaq Hasibuan; Suhela Putri Nasution; Anggun Triyoolanda; Irfan Rahman (Malikussaleh University, Aceh, Indonesia, 2023)
Empowerment is a pathway to participation, and participation determines the impact of community development programs socially and economically. In general, this study aims to identify the relationship between the level of community and stakeholder participation in implementing the Geothermal Agency's Corporate Social Responsibility Program through Microfinance Institutions and its impact on the socioeconomic conditions of the community. XYZ District-Based Microfinance Program partnering with LKMS. The subjects of this study were the people of XY Village, including local government and local communities, and company staff. The method applied in this research consists of quantitative and qualitative studies. With nine informants, fifty-five respondents were taken as samples representing the XY Village community. The results of this study indicate that each stakeholder has a different type and level of participation. The higher the story of the involvement of microfinance board members in each stage of program implementation, the higher the social and economic impact will be.